College and university administrators with disabilities: experiences in the workplace - Williams, Joie B., author; Quick, Donald Gene, advisor; Banning, James H., committee member; Valentine, Deborah, committee member; Dickmann, Ellyn M., committee member (Colorado State University. Libraries, 2010)
In recent years, Disability has been argued as a minority group, no longer the exclusive realm of individuals born with disabilities. Disability is defined as a permanent state or chronic condition. Disability can enter into a person's life at any time. As a minority status, disability shares similar experiences with other minority populations, including assumptions and stereotypes about those minority groups. Research on the experiences of women and people of color who work in higher education has echoed similar experiences and perceptions common to those of college students and college graduates with disabilities. Research on college administrators with disabilities has not been readily or widely researched. The purpose of this study was to address the research question: How do College and University Administrators describe their "lived experience with disabilities" in their workplace? Using a qualitative interpretive research approach, interviews were conducted with senior and mid-level college administrators with disabilities, from two and four year institutions, private and public. They were asked to discuss their experience of disability in the realm of their work. Three major themes were uncovered; living with disability, working with disability, and legacies. The findings suggested that many professionals with disabilities in higher education administration believe they are challenged by their non-disabled colleagues and peers based on their perceived limitations towards others with disabilities. While not all the participants of this study believed this, the majority of them acknowledged that at one time or another that they have all questioned the degree to which their colleagues have judged them based on their disabilities or their work performance. Several participants suggested that attitudinal behaviors on the part of nondisabled persons need to be challenged so that all people will be better informed before assumptions are made about limitations surrounding professionals with disabilities.
Keywords: Sociology of disability -- United States; Disabilities -- Social aspects -- United States; People with disabilities -- Employment -- United States; Discrimination against people with disabilities -- United States; Universities and colleges -- United States -- Administration